Relación entre el conocimiento sobre teoría de las necesidades de Maslow de los enfermeros asistenciales y el nivel de satisfacción de las necesidades del usuario alcanzados mediante la intervención de enfermería en el Hospital II Essalud Tarapoto Julio 2004 - Enero 2005 - Saavedra García, Katerine Margoth (2005)
A descriptive cross-sectional correlation based on the theory of human needs was performed according to Abraham Maslow's cua1 performed in the Hospital II ESSALUD Tarapoto; during the months of July 2004 to January 2005 to determine the relationship between knowledge of nurses on the theory of human needs according to Maslow and the level of customer satisfaction achieved through nursing interventions. The study sample consisted of 90 users and 15 nurses. For data collection instruments used as survey-interview satisfaction applied to users and a questionnaire on knowledge of needs Maslow developed by nurses. The data obtained were analyzed by the method of regression analysis, found that 52.2% of users reported being satisfied, 27.8% reported being dissatisfied. Dissatisfied 13.3% and only 6.7% reported being very satisfied with their basic needs. While the level of knowledge of nurses on the theory of human needs Maslow found that 66.7% of nurses have regular knowledge of the theory of human needs according to Maslow, 26.6% good knowledge and only 6.7 ° / o has poor knowledge. The varying level of knowledge of nurses about the theory of Maslow's human needs and level of user satisfaction relating to 94% depending on the statistical test of linear regression